Monitoring cell detachment by surfactants in a parallel plate flow chamber - Azeredo, Joana (2003)
The efficacy of the surfactants SDS and CTAB in detaching P. fluorescens from glass surface was evaluated in a parallel plate flow chamber. This device enables “in situ” determinations of cells detachment following the application of surfactants under well controlled hydrodynamic conditions. The results showed that SDS was able to remove almost all adhering bacteria in a short period of time, whereas CTAB did not promote much cell desorption. On the contrary, this surfactant increased the adhesion strength between cells and glass. Both surfactants promoted different alterations of cell surface properties, which explain their dissimilar effectiveness as cleansing agents.